Natural Plant Extracts as Acid-Base Indicator and Determination of Their pKa Value - N. Kapilraj; S. Keerthanan; M. Sithambaresan (Journal of Chemistry)
Commonly used indicators for acid-base titrations are synthetic, and this work was focused to identify the eco-friendly natural indicators and to determine their pKa values. The analytical potential of the flower extracts is very promising as seen in its application in acid-base titrimetry. These selected flower extracts were found to perform well in titrating strong acid-strong base than in weak acid-strong base. We have obtained a sharp and clear colour change from red to brownish yellow for the Bougainvillea glabra extract, from red to yellow for the Bauhinia purpurea extract, and from red to brownish yellow for the Impatiens balsamina extract. All the three flower extracts gave clear colour change with acids and bases, and the colour change was maintained with different acids and bases. The sharp contrast between their colours in acid and base made the pigment suitable for use as acid-base indicators. As these flower extracts have very simple,cost-effective, environment friendly extraction procedure and excellent performance with sharp colour change in end points of the titrations, it would be possible to replace the standard indicators being used in conventional laboratories with natural flower indicators.